Seleksi Pengolahan Sampah Secara Termal Menggunakan Life Cycle Assessment (LCA) di TPA Pakusari Kabupaten Jember - Dylan Mirza Kusumah (Fakultas Teknik, 2025)
The Controlled Landfill method at Pakusari Landfill is currently ineffective in accommodating the incoming waste due to the limited space they have, and the waste can emit Greenhouse Gases (GHGs) such as CH4 and CO2 gases. Therefore, a more effective waste management system or technology is needed. Thermal waste treatment technology is an alternative that can reduce the volume of waste by up to 80%. An analysis using LCA (Life Cycle Assessment) was conducted on the emissions produced by each thermal waste treatment technology, consisting of incineration, pyrolysis, and gasification. Pyrolysis treatment has the lowest environmental impact, with a GWP of 3.485,13 kg CO2eq, POCP of 0.27 kg C2H4eq, and AP of 38.27 kg SO2eq. Gasification treatment has a GWP of 36.512,31 kg CO2eq, POCP of 0.43 kg C2H4eq, AP of 34.48 kg SO2eq. Incineration treatment is more recommended to be implemented at Pakusari Landfill, with the addition of an air pollution control system (APC). The addition of APC system is necessary because incineration has the largest environmental impact, with a GWP of 35,859.48 kg CO2eq, POCP of 17.20 kg C2H4eq, and AP of 2,241.14 kg SO2eq. The APC system that can be added is Selective Catalytic Reduction to reduce NOx with up to 60% of reduction efficiency. The total cost that is needed for incineration treatment plant including unit investment, APC investment, and operational and maintenance is Rp 403.845.004.
Reaploud Repository Hasyim April 2026
Keywords: Environmental impact; Global Warming Potential; Incineration; LCA; Thermal waste treatment